2023
DOI: 10.1111/cas.15839
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium butyricum inhibits epithelial–mesenchymal transition of intestinal carcinogenesis through downregulating METTL3

Abstract: Colorectal cancer (CRC) is related to gut microbiota dysbiosis, especially butyrateproducing bacteria reduction. Our previous study suggested that administration of Clostridium butyricum, a butyrate-producing bacterium, exerts a crucial effect against CRC, however the potential mechanism is not clear. We first found that methyltransferase-like 3 (METTL3) showed a positive correlation with proliferation, epithelial-mesenchymal transition (EMT), DNA repair, metastasis, and invasion in a database analysis. The ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…It is worth noting that the role of butyrate and butyrate-producing bacteria, such as C. butyricum and F. prausnitzii , has also been examined concerning their contribution to EMT in oncogenesis. Indeed, studies have reported that butyrate could potentially mitigate the development of colorectal cancer, a formidable complication of UC, by modulating the Wnt/β-catenin pathway [ 130 ].…”
Section: Microbial Metabolites: Established Players In Intestinal Hom...mentioning
confidence: 99%
“…It is worth noting that the role of butyrate and butyrate-producing bacteria, such as C. butyricum and F. prausnitzii , has also been examined concerning their contribution to EMT in oncogenesis. Indeed, studies have reported that butyrate could potentially mitigate the development of colorectal cancer, a formidable complication of UC, by modulating the Wnt/β-catenin pathway [ 130 ].…”
Section: Microbial Metabolites: Established Players In Intestinal Hom...mentioning
confidence: 99%
“…Much of the data regarding the role of the gut microbiome/permeability in cancer has focussed on gastrointestinal cancer, where butyrate suppresses EMT [ 154 ] and cancer pathogenesis, as well as chemotherapy side-effects [ 155 ]. However, butyrate and the gut microbiome/permeability have relevant effects in a wide array of cancers, including breast cancer [ 156 ], glioblastoma [ 157 , 158 ] and ovarian cancer [ 159 ].…”
Section: Gut Microbiome Tumor and Mitochondrial Melatonergic Pathwaymentioning
confidence: 99%
“…However, butyrate and the gut microbiome/permeability have relevant effects in a wide array of cancers, including breast cancer [ 156 ], glioblastoma [ 157 , 158 ] and ovarian cancer [ 159 ]. The mode of butyrate efficacy is variably defined across studies, including via its capacity as an HDACi [ 160 ], especially as HDACi is a general target in cancer treatment [ 161 ], as well as via epigenetic regulation by GPR43 activation suppressing methyltransferase-like 3 (METTL3) [ 154 ] and cancer regulating miRNAs subsequent to HDACi [ 160 ]. However, butyrate also has direct effects on immune cells, indicating that its relevance in cancer pathogenesis, course and treatment may be significantly determined by its regulation of immune responses.…”
Section: Gut Microbiome Tumor and Mitochondrial Melatonergic Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Some enteric pathogens have been shown to be able to modulate EMT in IECs ( Table 5 ), such us Helicobacter pylori ( Yin et al, 2010 ; Ouyang et al, 2021 ), Citrobacter rodentium ( Chandrakesan et al, 2014 ), Escherichia coli ( Cane et al, 2010 ) or Clostridium butyricum ( Zhang et al, 2023 ), however these infections are not related with intestinal fibrosis.…”
Section: Emt Role In Intestinal Fibrosismentioning
confidence: 99%